Two-Sided Heterogeneity and Trade - Bernard, Andrew B.; Moxnes, Andreas; Ulltveit-Moe, Karen Helene (The Review of Economics and Statistics, 2018)
This paper develops a multicountry model of international trade that provides a simple microfoundation for buyer-seller relationships in trade. We explore a rich data set that identifies buyers and sellers in trade and establish a set of basic facts that guide the development of the theoretical model. We use predictions of the model to examine the role of buyer heterogeneity in a market for firm-level adjustments to trade shocks, as well as to quantitatively evaluate how firms’ marginal costs depend on access to suppliers in foreign markets.